If z = f(x,y)

(dz/dt) = (dx/dt) * (dz/dx) + (dy/dt) * (dz/dy)

Where dz/dx and dz/dy are partial derivatives.

I am not sure what fx(-5,1) = 1 and fy(-5,1) = -1 mean, but I guess they represent these partial derivatives. Summarizing the information until now:

g(1) = -5 –> x = -5 in this special case for t = 1

h(1) = 1 –> y = 1 in this special case for t = 1

g'(1) = -6

h'(1) = 1

for those specific values of x and y, the partial derivatives are:

dz/dx = 1

dz/dy = -1

Filling in gives:

(dz/dt) = (dx/dt) * (dz/dx) + (dy/dt) * (dz/dy)

dz/dt = -6 * 1 + 1 * -1

dz/dt = -6 – 2

dz/dt = -8

Edit: I have to admit, that’s a bit stupid :). Thanks for correcting me!